A Guiding Typology for Site Visits. Issue 156 (18th December 2017) - Chapman Haynes, Melissa; Murphy, Nora F.; Patton, Michael Quinn
Abstract: Site visits are an often‐implemented, understudied activity that occurs in the diverse contexts where program evaluation is conducted. Further, the purposes of evaluative site visits are varied, ranging from provision of technical assistance and formative learning to high‐stakes accreditation site visits. The purpose of this chapter is to set the stage for the rest of this New Directions for Evaluation volume by presenting a typology of site visits with examples that illustrate variations in the eight categories or characteristics of the proposed typology. The typology will help practitioners clarify their thinking around their own site visits and aid in the evaluation planning and design phase of their practice. Additional chapters in this volume will add to the typology by discussing various aspects of quality, procedures, and use of site visits.